Comparing Israeli attacks towards Gaza Strip before and after Palestine's accession to the ICC - Aldahshan, Said (International Journal of Scientific Research and Management (IJSRM), 2020)
In order to search for any changes in the number and type of Israeli attacks on the Gaza Strip after Palestine’s accession to the International Criminal Court, a statistical analysis was conducted comparing five years before joining from 2010 to 2014 versus five years after accession from 2015 to 2019. By relying on official statistics issued by the human rights centers, the comparison was made in 1- the numbers and types of the victims 2- The targets that these attacks hit, and the researcher found, that there was a significant decrease in the number of dead, from (2730) in the first period it decreased to (436) in the second period, In contrast to the number of wounded, which rose from (13948) to (22165) in the second period due to the Great Return March. When comparing the ratio of the dead to the wounded in each period, it was found that it was proportional to (51) wounded, for every (10) dead, which increased dramatically and became (508) wounded for every (10) killed. On the other hand, the number of hit targets from (59155) to (23,464). And the category of targeting cars and motorcycles from (1311) became only (4), which is a percentage closer to zero in this category. All of this confirms that Israel has changed the number and type of its attacks against the Gaza Strip, and the nature of the objectives it intended in both quality and quantity after Palestine joined ICC.